Crecimiento económico y desarrollo del mercado de capitales peruano: evidencia empírica 1989 -2019 - Razeto Rojas, Piero Fabrizzio (2023)
At the beginning of the 1990s, Peru went through strong political-economic changes, which caused a solid development of the financial system, directly including the capital market. Over the years, the impact that the development of the capital market has on long-term economic growth has been an issue that has had different results around different parts of the world, currently in Peru, due to the limitations regarding data collection, empirical modeling research focused on long-term causality has been little worked on, but in this research, we have been able to collect the amount of data necessary to establish a long-term causality model to determine the relationship of the development of the capital market and economic growth through a VEC modeling, which led us to the conclusion that if there is a long-term causality between the development of the capital market and economic growth in Peru, which would indicate that the change in the political context, starting in the 1990s, by directly influencing the capital market by making it develop and evolve through economic liberalization made up of the reopening of stock trading, the repeal of the nationalization of the financial system and inflationary stability; was positive for the economic growth of Peru and its development should be encouraged along with future research on the development of the Peruvian capital market to encourage future discussion.